Coronary Artery Disease Complexity on the Outcomes of a Staged Approach of PCI Followed by Minimally Invasive Valve Surgery. Issue 2 (March 2017) - Pineda, Andrés M.; Gowani, Saqib A.; Mihos, Christos G.; Chandra, Ramesh; Santana, Orlando; Lamelas, Joseph; Beohar, Nirat
Abstract : Objective: A staged approach of percutaneous coronary intervention (PCI) followed by minimally invasive valve surgery (MIVS) is an alternative to the combined coronary artery bypass graft and valve surgery for patients with concomitant coronary artery (CAD) and valvular heart disease. We sought to evaluate the impact of the complexity of CAD, as assessed by the Syntax score, on the outcomes of the staged approach. Methods: We retrospectively evaluated 138 patients who underwent PCI and MIVS at our institution between January 2009 and June 2013. The baseline Syntax score was calculated, and the patients were divided into two groups: low risk (Syntax scores, 0–22) or intermediate-high risk (>22). Results: There were 125 patients with low (mean ± standard deviation, 8 ± 5) and 13 with intermediate-high (mean ± standard deviation, 26 ± 4) Syntax scores. Baseline, PCI, and operative characteristics were similar between the groups, except for an observed higher incidence of peripheral arterial disease, multivessel coronary disease, mitral valve replacement, and a higher predicted The Society of Thoracic Surgeons mortality risk score in the intermediate-high Syntax group. The short-term postoperative complications, 30-day mortality, and 3-year survival (84% vs 77%) were similar between the groups. Patients in the intermediate-high–risk group had a higher incidence of repeat target vessel revascularization during follow-up (0.8% vs 16.7%). Conclusions: A staged approach of PCI followed by MIVS is a safe and feasible alternative for patients with valvular heart disease and concomitant CAD. However, it may confer an increased incidence of repeat target vessel revascularization in patients with intermediate- to high-complexity CAD.